Dynamic Spectrum Management (DSM) Algorithms for Multi-User xDSL - Huberman, S.; Leung, C.; Le-Ngoc, T. (IEEE Communications surveys and tutorials, 2012)
Dynamic Spectrum Management (DSM) is an effective method for reducing the effect of crosstalk in Digital Subscriber Line (DSL) systems. This paper discusses various DSM algorithms, including Optimal Spectrum Balancing (OSB), Iterative Spectrum Balancing (ISB), Autonomous Spectrum Balancing (ASB), Iterative Water-Filling (IWF), Selective Iterative Water-filling (SIW), Successive Convex Approximation for Low complExity (SCALE), the Difference of Convex functions Algorithm (DCA), and Distributed Spectrum Balancing (DSB). They are compared in terms of performance (achievable data rate) and computational complexity.